Impacts of future sea level change on Greenland from community knowledge, coastal mapping, and glacial isostatic adjustment models - Kirsty J. Tinto; Jacqueline Austermann; Robin E. Bell; David Blockley; Casey E. Brayton; Diana Krawczyk; Lauren Lewright; Andrew J. Lloyd; Frank O. Nitsche; Guy J. G. Paxman; David F. Porter; Aqqaluk Sørensen; et al. (Proceedings of the National Academy of Sciences, 2026)
Making predictions of global change relevant to individual communities is a critical challenge, especially where local impacts diverge from global predictions. While sea level is rising globally, in Greenland, sea level is predicted to fall over the coming century due to land rebound and sea surface lowering, consequences of glacial isostatic adjustment from both past and future ice loss. Here we present results of a US and Greenland scientific partnership, working with the community of Aasiaat, West Greenland, to identify the impacts of future sea level change where sea level is projected to fall 0.41 to 0.93 m by 2100 CE. Through collaboratively designed, conducted, and interpreted multibeam bathymetry surveys combined with targeted glacial isostatic adjustment models, we identify areas that will be most impacted by sea level fall. We identify two shallow channels where disruption to navigation and nutrient cycles will occur when water level falls beneath critical depth thresholds. To make these predictions useful we established communication pathways to share findings effectively across a broad array of interest groups by engaging with community members, government officials, and students. This multipronged approach of collaboratively designed observations, locally targeted impact modeling and integrated formal and informal communication can be expanded to coastal communities facing environmental challenges around the world.